PHYSICAL MODELING OF THE MAGNETOTELLURIC FIELD IN THE PETROPAVLOVSK GEODYNAMIC SITE, KAMCHATKA - Moroz Y.F.; Kobzova V.M.; Ladanivskii B.T. (My University, 2000)
The effects of surface resistivity inhomogeneities on magnetotelluric sounding (MTS) curves under the complex geologic conditions of the Site were examined. Three-dimensional models were used to imitate a resistivity structure close to the real one and to reveal the basic features in the MTS curves caused by the "coast" effect, by a transverse conductivity structure in the sediments, by the complex coastline, and by the presence of volcanoes. It is shown that MTS curves oriented along Kamchatka should preferably be used to study deep electric conductivity in the Site area. However, these curves are also affected by surface resistivity inhomogeneities. Low frequency distortions of MTS curves were estimated for different geoelectric conditions at the Site. These results can be used in the interpretation of practical MTS curves.